Computational strategies for PROTAC drug discovery - Jia Wu; Wanhe Wang; Chung-Hang Leung (Acta Materia Medica)
Proteolysis-targeting chimeras (PROTACs), a novel targeted protein degradation technology for potential clinical drug discovery, is composed of a protein-targeting ligand covalently linked to an E3 ligase ligand. Through recruiting E3 ligase to target proteins, PROTACs elicit ubiquitination and subsequent degradation of targets via the ubiquitin-proteasome system. In the past few decades, molecular docking and virtual screening have emerged as an efficient strategy in drug discovery for identifying compounds from a large database of chemical structures. For PROTACs, molecular docking accurately simulates the protein-PROTAC-E3 ternary complex, thus greatly accelerating structure-activity-relationship analysis, and improving ligand affinity and selectivity. In this review, we summarize recent efforts in the application of molecular docking and virtual screening for PROTAC drug discovery. To date, approximately nine target proteins and twelve PROTACs have been successfully developed through molecular docking and virtual screening. Finally, the potential challenges of molecular docking and virtual screening-based PROTACs are discussed.